Outcomes of damage control laparotomy after trauma in low andmiddle-income countries: A systematic review and meta-analysis - Shumani Makhadi; Vukosi Baloyi; Emmanuel Ekene Nweke; Maeyane Stephens Moeng (PLoS ONE, 2026)
Background Damage control laparotomy (DCL) is an established life-saving strategy for critically injured patients presenting with the lethal triad of hypothermia, acidosis, and coagulopathy. While outcomes in high-income countries (HICs) are well documented, evidence from low- and middle-income countries (LMICs), as classified by the World Bank, remains fragmented. This systematic review synthesises available evidence on DCL outcomes in LMICs. Methods A systematic search of PubMed, Scopus, Google Scholar, the Cochrane Library, and African Journals Online was conducted from January 2004 to February 2026. Studies reporting mortality outcomes after DCL for civilian trauma in World Bank–classified LMICs were included. Proportional meta-analysis using a DerSimonian-Laird random-effects model with logit-transformed proportions was performed. The protocol was prospectively registered on PROSPERO (CRD42025639498). The detailed search strategy is provided in S1 Table. Results Ten retrospective studies comprising 914 patients from five countries (South Africa, Pakistan, India, Oman, and Brazil) met the inclusion criteria. Six of the ten studies (n = 704, 77.0%) were from South Africa. The pooled mortality rate was 37.77% (95% CI: 31.38%–44.62%; 95% prediction interval: 20.1%–59.1%), with substantial heterogeneity (I² = 74.46%), based on 327 deaths among 914 patients. Subgroup analysis showed a pooled mortality of 31.61% (95% CI: 28.27%–35.15%, I² = 0.00%) in South African studies and 53.62% (95% CI: 44.47%–62.54%, I² = 31.65%) in non–South African LMIC studies (Cochran Q-test for subgroup differences: Q = 14.23, df = 1, p < 0.001). Conclusions DCL mortality in LMICs appears higher than mortality rates reported in HIC series, though direct comparison is limited by differences in study populations, injury profiles, case-mix, and the predominance of South African data in the available literature. The pooled estimate should be interpreted cautiously given the small number of studies, high heterogeneity, and retrospective study designs. Pre-hospital care, emergency theatre access, blood banking infrastructure, ICU capacity, and infection prevention represent potential areas for targeted improvement. Further prospective, multi-centre studies with standardised outcome definitions are needed to better characterise DCL outcomes across diverse LMIC settings.